2023
DOI: 10.1037/cbs0000297
|View full text |Cite
|
Sign up to set email alerts
|

Is the messenger the message? Canadian political affiliation and other predictors of mask wearing frequency & attitudes during the COVID-19 pandemic.

Abstract: We used a longitudinal design to examine factors associated with Canadians' (1) early adoption of maskwearing and (2) attitudes toward mask mandates before mandatory mask mandates were issued. In May 2020, 1,712 Canadians began a 28-day daily diary study tracking their experiences with the COVID-19 pandemic. We examined the associations between people's political affiliation, psychological reactance, pre-existing risk factors, attitudes about the pandemic's severity, attitudes about mask mandates, and public m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…If males potentially are more likely to be anti-mask, then a larger female sample size may have an impact on our results. Some studies reported that slightly older males are more likely to be anti-mask, while others found no significant impact of gender on mask-wearing attitudes and behaviors (Courtice et al, 2023;Howard, 2021). The gender analysis of the current sample did not indicate any influence of gender on the pro-or anti-mask attitudes or behaviors.…”
Section: Limitations and Future Directionscontrasting
confidence: 70%
See 3 more Smart Citations
“…If males potentially are more likely to be anti-mask, then a larger female sample size may have an impact on our results. Some studies reported that slightly older males are more likely to be anti-mask, while others found no significant impact of gender on mask-wearing attitudes and behaviors (Courtice et al, 2023;Howard, 2021). The gender analysis of the current sample did not indicate any influence of gender on the pro-or anti-mask attitudes or behaviors.…”
Section: Limitations and Future Directionscontrasting
confidence: 70%
“…Courtice and colleagues (2023) found that prior to the first public statements from the Canadian government regarding masking, beliefs about the severity of the pandemic were positively related to both mask wearing and attitudes about mask mandates. In addition, those who faced an increased risk of severe COVID-19 due to pre-existing health conditions reported more frequent mask wearing (Courtice et al, 2023). Women also initially reported higher mask wearing than men, however, subsequent studies have failed to find a link between gender and mask-wearing behavior, suggesting that gender is not a consistent predictor of mask-wearing behavior (Courtice et al, 2023;Howard, 2021).…”
Section: Face Masks and Social Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth considering how attitudes toward the pandemic may overshadow concerns relating to immigration or for the border closure more broadly. Across both countries, citizens with right-leaning or conservative orientations tend to express less concern for the public health crisis and greater reluctance to comply with precautionary measures (Clinton et al 2021;Courtice et al 2021;Druckman et al 2021). These same groups of individuals tend to favor restrictionist border policies (Gravelle 2018b) like the one that Trudeau and Trump implemented to help mitigate COVID.…”
Section: Discussionmentioning
confidence: 99%